Prosfektif Metode Sampel Darah Kering dalam Bioanalisis - Supandi Supandi (Journal of Tropical Pharmacy and Chemistry, 2016)
Biosampling of dried blood spot method became lately very interested in bioanalysis, some of the advantages given in this method compared to conventional venous canulla (venipuncture); less invasive making it more pleasant for the patient or subject, requires small volume, requires simple transportation process and storage did not need special equipment, suod stabilizes analit and reduces risk of infection. The method of dried blood spot is done by invasive light on the finger or heel prick and then spike on filter paper and dried at room temperature or under nitrogen flow with controlled humidity and stored in bag with desiccant packages, than it analyzed using validation bioanalyzing method. Dried blood spot method can be applied on bioanalysis test for pharmacokinetic, toksikokinetic , epidemiologic and Teurapeutic drug monitoring.